2016
DOI: 10.12944/crnfsj.4.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Dietary knowledge Among Female Diabetic Patients in Amman, Jordan

Abstract: The aim of this study was to assess dietary knowledge among females with diabetes in Amman, Jordan. We performed a cross-sectional study of diabetic patients attending outpatient diabetes clinics, at several hospitals in Amman . A questionnaires and 24-hour dietary recall were completed by the participants. The study used a face to face interview during which a questionnaire was filled by the investigator about knowledge and attitudes of diabetic patients. The study sample was composed of 180 females. Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 23 publications
1
22
1
Order By: Relevance
“…A total of 32 studies were eligible and included in this review focusing on the barriers to good glycemic control and adherence to diabetes management plan in adults with T2DM in Jordan. Of these 32 studies, 13 discussed issues related to Type 1 diabetes and T2DM,8,14–16,31,35,42,43,53–57,71 while 13 focused on T2DM only 10,11,17,19,21,25,29,33,34,44,45,48,56. Four of the studies addressed other long-term diseases alongside diabetes,26,50,51,70 and two studies focused on lifestyle issues and diabetes-risk factors 18,41.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 32 studies were eligible and included in this review focusing on the barriers to good glycemic control and adherence to diabetes management plan in adults with T2DM in Jordan. Of these 32 studies, 13 discussed issues related to Type 1 diabetes and T2DM,8,14–16,31,35,42,43,53–57,71 while 13 focused on T2DM only 10,11,17,19,21,25,29,33,34,44,45,48,56. Four of the studies addressed other long-term diseases alongside diabetes,26,50,51,70 and two studies focused on lifestyle issues and diabetes-risk factors 18,41.…”
Section: Resultsmentioning
confidence: 99%
“…Lack of knowledge about healthy behaviors, high energy dense diet, the role of social activities that are associated with consuming a high-calorie dense food, sedentary lifestyle and physical inactivity 12. As populations in Jordan become more urbanized, and as lifestyles shift towards increased physical inactivity and increased food consumption, the prevalence of obesity and overweight is expected to rise 8. The prevalence rates of overweight and obesity among children and adolescents in Jordan were 21.6% and 10.2% in 2012, respectively, 23.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing our study results with those of the Iranian study, our patients also had poor DK. A study done by El-Qudah [15] revealed an inadequate DK in diabetes patients. Furthermore, the author recommended to set up health education programs on DM with a special emphasis on self-monitoring training.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, the quantitative score variable was categorized in percentage. A score <50% was considered as having poor DK, whereas, a score between 50%-75% was considered as having good DK, and a score >75% was considered as having adequate DK [14][15][16]. The DKQ was also translated into the Arabic language by an expert using the back-translation technique.…”
Section: Methodsmentioning
confidence: 99%
“…Family history was the most common risk factor reported by patients in this study. Similarly, a study reported that 126 (70 %) had a family history of diabetes as a first-degree family member in Jordan [5].…”
Section: Responsibility Towards One's Health Is Emphasized In the Qurmentioning
confidence: 96%